Efficacy and Safety of Placebo During the Maintenance Therapy of Ovarian Cancer in Randomized Controlled Trials: A Systematic Review and Meta-analysis - Wang, Jin-feng; Zhao, Lan-bo; Bin, Ya-di; Zhang, Kai-lu; Sun, Chao; Wang, Yi-ran; Feng, Xue; Ji, Jing; He, Li-song; Chen, Fang-yao; Li, Qi-ling (Frontiers in Oncology, 2022)
Introduction: This meta-analysis evaluated the efficacy and safety of placebo during the maintenance therapy of ovarian cancer (OC) patients in randomized controlled trials (RCTs). Methods: A comprehensive literature review was searched for RCTs published up to and including August 2020 from four electronic databases. We analyzed efficacy and safety in control arms during the maintenance therapy in advanced OC patients. Hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) of progression-free survival (PFS) and overall survival (OS) were estimated in placebo arms and observation arms, respectively, using Frequency Framework method. We also calculated the incidences of common adverse effects (AEs) in placebo arms. Results: Total 43 41 articles with 21,03220,099 (4,787918 in placebo arms, 3,420688 in observation arms and 11,89212,426 in experiment arms) patients were included in this meta-analysis. Compared with observation, placebo did not improve or reduce PFS (HR, 1.02; 95% CI, 0.87-1.1920; P = 0.8081) and OS (HR, 1.024; 95% CI, 0.9389-1.1716; P = 0.7651) of OC patients, other treatment except for radiotherapy significantly improved PFS and OS (all P ˂ 0.05). The incidences of AEs produced by placebo were 94.033.82% in all grades and 20.202% in grade ≥ 3. The incidences of AEs were 30.5529.75% in fatigue, 27.3926.38% in nausea, 24.343.98% in abdomen pain, 18.926% in constipation, 17.2616.65% in diarrhea, 14.556% in vomiting, 13.89% in hypertension and 13.1487% in headache. Conclusions: Placebo did not improve or reduce PFS and OS benefits of OC patients in RCTs, but it increased the incidences of AEs.